Dual bombard by Cytomegalovirus and Mycobacterium tuberculosis in a renal transplantee - Cinthujah Balachander; Indira Ananthapadmanabasamy; Ramasubramanian Viswanathan; Poongodi Santhanakumarasamy (Journal of Current Research in Scientific Medicine)
In the first year following an organ transplant, more than 80% of patients encounter a minimum of one occurrence of infection. Here, we report a case of coinfection of the Cytomegalovirus (CMV) and Mycobacterium tuberculosis (MTB) in a kidney transplantee. Computed tomography chest (CT chest) showed bilateral ground-glass opacities. By Cytomegalovirus DNA polymerase chain reaction, 9360 copies were detected in plasma. Cartridge-based nucleic acid amplification test from bronchial washings tested positive for MTB with very low-level resistance to rifampicin. He was started on category-I antitubercular therapy without rifampicin and intravenous valganciclovir. The clinical status of the patient improved after 1 month of treatment.